Islamisasi Ilmu Pengetahuan Menurut Syed M. Naquib Al-Attas dan Ekspansinya dalam Pendidikan di SMA NU 1 Model Lamongan: The Islamization of Knowledge According to Syed M. Naquib Al-Attas and Its Expansion in Education at SMA NU 1 Model Lamongan - Evy Nur Rohmawaty; Ahmad Syafa'at Junaidi; Mira; Abdullah (AL-QIBLAH: Jurnal Studi Islam dan Bahasa Arab, 2026)
The Islamization of knowledge emerged from the concerns of Muslim intellectuals regarding an epistemological crisis experienced by the Muslim community, caused by the infiltration of Western knowledge driven by secular motives that are considered incompatible with Islamic values. This study aims to describe the expansion and integration of knowledge and religion at Nahdlatlatul Ulama Senior High School (SMA NU) Modern and Religius Lamongan. Therefore, this research employs a library research approach using a qualitative method in order to draw conclusions from the research findings. Data collection techniques in this study include observation and documentation. Based on the results of the discussion, it can be concluded that the educational curriculum at SMA NU 1 Model Lamongan integrates religious knowledge and science through an integrative scientific paradigm. Furthermore, the Islamization of knowledge is implemented through classroom learning, religious extracurricular activities such as banjari or sholawat and manaqib, in-depth studies of the Qur’an and Hadith, as well as spiritual activities conducted before the learning process begins, including the recitation of the Qur’an.